Organizational culture and academic staff satisfaction in Somaliland higher education: evidence from structural equation modeling - Cumar, Mukhtaar Axmed; Kidaneb, Befekadu Zeleke; Golgac, Dawit Negassa; Dinsa, Feyera (Frontiers in Education, 2025)
IntroductionThis study examines the influence of organizational culture (OC) on academic staff job satisfaction (JS) within higher education institutions (HEIs) in the unique post-conflict context of Somaliland. The research highlights the importance of aligning organizational culture with faculty needs to improve retention, motivation, and institutional effectiveness.MethodsUsing data from 266 academic staff and guided by the Competing Values Framework (CVF), four culture types—Collaborate (Clan), Create (Adhocracy), Compete (Market), and Control (Hierarchy)—were assessed alongside three dimensions of job satisfaction: General (GJS), Intrinsic (IJS), and Extrinsic (EJS). Structural Equation Modeling (SEM) was employed to analyze the predictive relationships.ResultsDescriptive results showed that Control (M = 3.66, SD = 0.66) and Collaborate (M = 3.62, SD = 0.75) cultures were the most prevalent. Intrinsic job satisfaction (M = 3.64, SD = 0.52) was the highest reported satisfaction facet, while extrinsic satisfaction (M = 3.32, SD = 0.74) was the lowest. The SEM analysis revealed that Collaborate culture significantly predicted all three satisfaction dimensions (β = 0.50–0.74, p < 0.05). Create and Compete cultures positively influenced IJS and EJS, while Control culture enhanced GJS (β = 0.32, p < 0.05) and IJS (β = 0.46, p < 0.05) but had a non-significant negative effect on EJS.DiscussionThese findings suggest that collaborative, innovative, and structured environments foster job satisfaction in various forms, though their impact varies across satisfaction domains. The study underscores a crucial psychological tension between the institutional need for structural stability and the academic staff’s inherent need for professional autonomy and recognition, offering key insights for institutional leaders and policymakers in Somaliland.